A new perspective of probing the level of pollution in the megacity Delhi affected by crop residue burning using the triple oxygen isotope technique in atmospheric CO2. (August 2020) - Laskar, Amzad H.; Maurya, Abhayanand S.; Singh, Vishvendra; Gurjar, Bhola R.; Liang, Mao-Chang
Abstract: Air quality in the megacity Delhi is affected not only by local emissions but also by pollutants from crop residue burning in the surrounding areas of the city, particularly the rice straw burning in the post monsoon season. As a major burning product, gaseous CO2, which is rather inert in the polluted atmosphere, provides an alternative solution to characterize the impact of biomass burning from a new perspective that other common tracers such as particulate matters are limited because of their physical and chemical reactiveness. Here, we report conventional ([CO2 ], δ 13 C, and δ 18 O) and unconventional (Δ 17 O) isotope data for CO2 collected at Connaught Place (CP), a core area in the megacity Delhi, and two surrounding remote regions during a field campaign in October 18–20, 2017. We also measured the isotopic ratios near a rice straw burning site in Taiwan to constrain their end member isotopic compositions. Rice straw burning produces CO2 with δ 13 C, δ 18 O, and Δ 17 O values of −29.02 ± 0.65, 19.63 ± 1.16, and 0.05 ± 0.02‰, respectively. The first two isotopic tracers are less distinguishable from those emitted by fossil fuel combustion but the last one is significantly different. We then utilize these end member isotopic ratios, with emphasis on Δ 17 O for the reason given above, for partitioning sources that affect the CO2 level in Delhi. Anthropogenic fraction of CO2 at CP ranges from 4 to 40%. Further analysis done by employing a three-component (background, rice straw burning, and fuel combustion) mixing model with constraints from the Δ 17 O values yields that rice straw burning contributes as much as ∼70% of the total anthropogenic CO2, which is more than double of the fossil fuel contribution (∼30%), during the study days. Graphical abstract: Image 1 Highlights: 17 O excess in CO2 is a potentially useful tracer for atmospheric pollution study. δ 13 C, δ 18 O and Δ 17 O values of rice straw burned CO2 are −29.02, 19.63, and 0.05‰. Post monsoon rice straw burning is a major source of pollution in Delhi. Rice straw burning contributes more than 2/3rd of anthropogenic CO2 in winter Delhi.